2019
DOI: 10.11604/pamj.2019.33.181.13928
|View full text |Cite
|
Sign up to set email alerts
|

Thrombocytopenia with absent radii (TAR) syndrome in a female neonate: a case report

Abstract: Thrombocytopenia absent radius (TAR) syndrome is a rare congenital disorder that is consistently associated with skeletal abnormality and thrombocytopenic haemorrhage. This is a case of a neonate with bilateral absent radius and thrombocytopenia. The rarity of this case prompted this report.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
1
3
1
Order By: Relevance
“…Significant laboratory findings in TAR syndrome include a platelet count less than 50 000 plt/ml with normal platelet morphology on peripheral blood film examination. Other associated hematological features are eosinophilia, leukocytosis with a left shift 8 , all these features are seen in our case.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Significant laboratory findings in TAR syndrome include a platelet count less than 50 000 plt/ml with normal platelet morphology on peripheral blood film examination. Other associated hematological features are eosinophilia, leukocytosis with a left shift 8 , all these features are seen in our case.…”
Section: Discussionsupporting
confidence: 72%
“…The sex ratio of diagnosed cases was 1:1 6 . Although other studies reported female’s predilection 8 ( female patient in our case).…”
Section: Discussioncontrasting
confidence: 57%
“…Diagnosis of the syndrome can occur prenatally by ultrasound and platelet count via fetal blood sampling via cordocentesis [10]. At birth, the absence of radii and the presence of thrombocytopenia, with or without other manifestations of TAR, are considered hallmarks of a positive diagnosis [6].…”
Section: Discussionmentioning
confidence: 99%
“…Upon diagnosis of TAR syndrome, the thrombocytopenia can be quite severe; approximately 95% of patients with the condition have a platelet count of <50,000/uL, normalizing over time in most patients [4]. Immediately after birth, approximately 50% of infants with TAR syndrome have symptomatic thrombocytopenia, and by four months of life, 90% will be symptomatic [6]. TAR syndrome has also been found to increase the occurrence of anomalies within hematologic, cardiovascular [4], gastrointestinal, and skeletal systems [7].…”
Section: Introductionmentioning
confidence: 99%
“…TAR syndrome has no gender, ethnic, or racial predilection 7 but some studies have reported females' predilection. 7 We present a child with TAR syndrome with tetralogy of Fallot (TOF) who underwent intracardiac repair (ICR). The child manifested features of hypothyroidism postoperatively which was a new find with this syndrome, not reported previously.…”
Section: Introductionmentioning
confidence: 99%